Bringing Vision-Based Measurements into our Daily Life: A Grand Challenge for Computer Vision Systems - Scharcanski, Jacob (Frontiers in ICT, 2016)
Bringing computer vision into our daily life has been challenging researchers in industry and in academia over the past decades. However, the continuous development of cameras and computing systems turned computer vision based measurements into a viable option, allowing new solutions to known problems. In this context, computer vision is a generic tool that can be used to measure and monitor phenomena in wide range of fields. The idea of using vision based measurements is appealing, since these measurements can be fast and easy to obtain and handle by humans. On the other hand, these vision based measurements need to be at least as precise and accurate as those obtained by more traditional measuring systems. This article discusses the perspectives and challenges of introducing vision based measurements into our daily life.